2014
DOI: 10.1007/s10803-014-2114-x
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Are Autistic-Behaviors in Children Related to Prenatal Vitamin Use and Maternal Whole Blood Folate Concentrations?

Abstract: Prenatal multivitamin/folic acid supplement use may reduce the risk of autism spectrum disorders. We investigated whether 2nd trimester prenatal vitamin use and maternal whole blood folate (WBF) concentrations were associated with Social Responsiveness Scale (SRS) scores at 4-5 years of age in a prospective cohort of 209 mother-child pairs. After confounder adjustment, children born to women taking prenatal vitamins weekly/daily (n=179) had lower odds of clinically elevated SRS scores (odds ratio:0.26; 95% con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 27 publications
2
64
0
2
Order By: Relevance
“… obtained similar results from Iranian children. A reduction in autistic traits was also observed by some authors in children aged 5–6 following the prenatal use of folic acid, even though ASD was not diagnosed. On the other hand, although some major studies have found that folic acid use before and during pregnancy was associated with a reduced risk of ASD in children, others have not .…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“… obtained similar results from Iranian children. A reduction in autistic traits was also observed by some authors in children aged 5–6 following the prenatal use of folic acid, even though ASD was not diagnosed. On the other hand, although some major studies have found that folic acid use before and during pregnancy was associated with a reduced risk of ASD in children, others have not .…”
Section: Discussionsupporting
confidence: 60%
“…Diagnoses were reported according to the Diagnostic and Statistical Manual of Mental Disorders and the International Classification of Diseases Criteria . The Social Responsiveness Scale was used to assess autistic traits in one study .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…mothers of neurotypical children; James et al, 2010). Another recent study found no association between maternal whole blood folate levels and autistic behavior in their children (Braun et al, 2014).…”
Section: Fa/methyl Donor Intake and Asdmentioning
confidence: 96%
“…One study of interactions showed folic acid protection against pesticide-related increased risk of ASD. Schmidt et al [2011Schmidt et al [ , 2012Schmidt et al [ , 2017; Suren et al [2013]; Braun et al [2014a]; Steenweg-de Graaff et al [2015]; Virk et al [2016] Maternal iron In a large case-control study, mothers of children with ASD were less likely to report taking an iron supplement; lowest quintile of supplemental iron associated with ASD, especially in older mothers and mothers with metabolic conditions. A large birth cohort found no association with minerals.…”
Section: Ipimentioning
confidence: 99%